Debt fnancing and firm performance: an analysis of Securities Commission of Malaysia 2013 revised shariah approved firms screening method - Ramli, Nurshamimitul Ezza; Ghani, Gairuzazmi; Haron, Razali; Che Embi, Nor Azizan (COMSATS University !sl1J11abad, Lahore Campus, Pakistan, 2020)
This study aims to assess the impact of the revised Shariah approved firms screening method in relation to the levels of debt and the Shariah-approved firms' performance introduced by the Securities Commission (SC) of Malaysia in 2013. The period of the study is 2000 to 2014. Panel regressions were employed to examine the impact for the firms that are consistently Shariahapproved as determined by the SC of Malaysia. The regression result indicates a non-monotone association between Shariah-approved firms' performance and debt levels. The optimum level of debt, however, is much higher than the 33% benchmark set by SC. Therefore, it can be concluded that the 2013 revised Shariah- approved firms screening method, which introduced the 33% debt ratio benchmark, did not improve the performance of Shariah-approved firms for the period studied. Nevertheless, since the observations are only until 2014, it is possible that the observations might not have captured the true impact of the change.